Prophylactic add-on antiplatelet therapy in chronic kidney disease with type 2 diabetes mellitus: Comparison between clopidogrel and low-dose aspirin - Amitabh Dash; Rituparna Maiti; Tejaswi Kumar Akantappa Bandakkanavar; Amit Bhaskar; Jai Prakash; Bajarang Lal Pandey (International Journal of Preventive Medicine, 2013)
Background: Chronic kidney disease (CKD) coexisting with type 2 diabetes mellitus (DM) leads to coronary artery disease. The present study compares clopidogrel and low-dose aspirin as prophylactic therapy against coronary events in patients with CKD with diabetes. Methods: Total 80 patients of CKD with type 2 DM were randomized and allocated to clopidogrel and aspirin groups to receive the drug at a dose of 75 mg and 150 mg once daily respectively for 8 weeks as add-on therapy. Main outcome was change in blood pressure, metabolic parameters, renal function, inflammatory biomarkers, platelet aggregability and (UKPDS) United Kingdom Prospective Diabetes Study risk scoring. Results: Significant decrease in blood pressure (P < 0.01), total cholesterol (P = 0.02), LDL (P < 0.01), triglyceride (P < 0.01) and a better glycemic control (P < 0.01) was found in clopidogrel group. Renal markers and electrolytes have been improved in clopidogrel group but in aspirin group there was deterioration (2.5%) of creatinine clearance. Clopidogrel group has shown a significant decrease in hsCRP (P < 0.01), UKPDS risk scoring (P < 0.01) and better anti-aggregatory effect. Conclusions: Clopidogrel has prophylactic role in CKD with type 2 DM due to better control of metabolic parameters, renal function and inflammatory burden in comparison to aspirin.